Gingival Vascular Hamartoma In Relation To Maxillary Primary First Molar Region Of Pediatric Patient: A Case Report (International Journal of Environmental Sciences, 2025)
Oral hamartoma is a benign developmental malformation of tissue native to the oral cavity, most often detected in childhood, and managed effectively with surgery if needed. Gingival hamartomas are rare benign proliferations of disorganized local tissue. Few cases are reported in pediatric patients, particularly associated with primary teeth.A 7 years-old male patient reported with a swelling which was well defined, reddish in colour and 8mm x 5mm when measured over the buccal mucosa extending from the mesial aspect of tooth number 53 up to mesial aspect of tooth number 55. Surgical excision was carried out and sent for histopathological examination. It revealed hamartomatous lesion predominantly vascular with pronounced secondary changes including ulceration, haemorrhage and infection. Head and neck hamartomas have shown that these benign entities may expand and recur, and chronic inflammation may heighten the risk of malignant transformation. Early diagnosis and management are needed.